2019
DOI: 10.1242/jeb.191916
|View full text |Cite
|
Sign up to set email alerts
|

Body condition impacts blood and muscle oxygen storage capacity of free-living beluga whales (Delphinapterus leucas)

Abstract: Arctic marine ecosystems are currently undergoing rapid environmental changes. Over the past 20 years, individual growth rates of beluga whales (Delphinapterus leucas) have declined, which may be a response to climate change; however, the scarcity of physiological data makes it difficult to gauge the adaptive capacity and resilience of the species. We explored relationships between body condition and physiological parameters pertaining to oxygen (O 2 ) storage capacity in 77 beluga whales in the eastern Beaufo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 80 publications
1
14
0
Order By: Relevance
“…The aerobic dive limit (ADL) of adult belugas with a high body condition index is estimated at 17.4 min (Choy et al, 2019), which is close to the average dive durations of the two deepest dive classes reported here (Deep Benthic = 16.25 min and Deep Pelagic V = 17.25 min, Table 2). Deep Pelagic W dives were instead shorter than the belugas' ADL on average, and rarely exceeded this limit (median duration = 13.75 min, see Table 2).…”
Section: Foraging Divessupporting
confidence: 79%
“…The aerobic dive limit (ADL) of adult belugas with a high body condition index is estimated at 17.4 min (Choy et al, 2019), which is close to the average dive durations of the two deepest dive classes reported here (Deep Benthic = 16.25 min and Deep Pelagic V = 17.25 min, Table 2). Deep Pelagic W dives were instead shorter than the belugas' ADL on average, and rarely exceeded this limit (median duration = 13.75 min, see Table 2).…”
Section: Foraging Divessupporting
confidence: 79%
“…In marine mammals, the amount of muscle O 2 has traditionally been calculated by measuring the Mb concentration (g Mb • 100g −1 muscle) at a single location within a primary locomotor muscle and assuming a homogeneous distribution of Mb across all the body's muscles. Most previous studies have calculated total Mb from a single biopsy or muscle sample extrapolated to the locomotor muscle mass (epaxial group, hypaxial group and rectus abdominis) or the entire muscle mass, e.g., [13][14][15][16][17]. Nevertheless, several studies have shown significant differences in Mb concentration between muscles [18][19][20][21] and even within a single muscle [22][23][24] in marine mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Belugas are diving deeper and longer during foraging (Hauser 2016;Stafford et al 2016) and it is unknown if this will push animals-such as smaller belugas, which make shallower, shorter dives, with longer inter-dive intervals at the surface (Heide-Jørgensen et al 1998)-past their physiological limits. Reduced dive ability has also been linked to reduced O 2 stores in animals with poor body condition (Choy et al 2019). Poor nutrition affects both dive ability and immune function (e.g., Chandra 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite belugas' increased blood O 2 stores, Hedrick & Duffield (1991) report limited O 2 transport and conclude that belugas may be limited in their activity level (speed) during a dive. Belugas also possess increased capacity for muscle O 2 storage (myoglobin), muscle buffering capacity, red blood cell counts, haemoglobin and haematocrit, which have been reported to reach mature levels prior to weaning in belugas, which is faster than observed in other marine mammals (Noren & Suydam 2016;Noren et al 2018;Choy et al 2019).…”
Section: Beluga Dive Physiologymentioning
confidence: 99%